Miscellaneous newly recognized types of CNS tumors in the WHO CNS5 classification (other than gliomas, glioneuronal and embryonal tumors) - Debajyoti Chatterjee; Kirti Gupta (Wolters Kluwer Medknow Publications, 2022)
In this review, we describe salient features of a few of the newer entities recognized in the fifth edition of World Health Organization (WHO) classification of central nervous system (CNS) tumors. While most of these have been offshoots of the deoxyribonucleic acid (DNA) methylation profiling of CNS tumors with distinct profiling such as desmoplastic myxoid tumor (DMT) of the pineal region, SMARCB1-mutant, these also demonstrate subtle, distinct morphological features, which should be carefully searched for to diagnose them.